The Effect of Cervical Collar on Standing Balance in Different Positions of Head and Neck - Iman Rezaei; Mohsen Razeghi; Shohreh Taghi-Zadeh; Haleh Ghaem (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: Patients suffering from neck pain are usually advised to wear a cervical collar in an attempt to relieve symptoms of pain and muscle spasm or to limit neck movements. However, little information is available on the effect of wearing a collar on postural stability. The purpose of this study was therefore, to investigate the effect of cervical collar in neutral and 20 degrees extension of head and neck on balance. Materials & Methods: In this Quasi-experimental study, 36 healthy subjects volunteered to take part in the study through convenient simple sampling method. Data on anteropoterior (AP) and mediolateral (ML) displacement of center of pressure (COP) and AP, ML and total sway velocity were collected in four different test positions of neutral head and neck with and without cervical collar and extended head and neck with and without cervical collar. Paired Sample T-test was employed for statistical evaluation. Results: No statistically significant different (P<0. 05) was found between collar and no collar positions. The same result was achieved when neutral and extended positions were compared. Only a significant ML sway velocity (P=0. 043) was measured in extended head and neck position with collar compared to the neutral position. Conclusion: Results of this study can be concluded to indicate the deteriorating effect of wearing a cervical collar in extended position on standing balance, supporting a combined effect of decreased neck proprioception and disrupted vestibular function. So, patients should be advised to wear suitable cervical collar tailored to their appropriate neck size.